Inca geographical horizon (Revista de Crítica Literaria Latinoamericana, 2016)
I attempt to answer this question: What were the borders of kay pacha (this world) as seen from Cuzco? The results of the analysis of a few existing Andean sources and of some Spanish ones indicate that Tawantin Suyu in its broadest dimension referred to all of South America, and kay pacha also included Mexico, imagined as islands in the Pacific Ocean, and perhaps the Polynesian islands too.
Keywords: Cuzco; kay pacha; Tawantin Suyu; upa runa; Mexico; Polynesia